WORLDVIEW AND IDEOLOGY: PHILOSOPHICAL AND ETHICAL ANALYSIS - Morozov, Andriy; Hudkov, Serhiy (Ukrainian Cultural Studies, 2023)
The article provides an ethical analysis of worldview and ideology. It is noted that the moral and humanistic function of worldview is to form and preserve the individual "Self" in harmonious co-existence with other people, not to dissolve its singularity in the totality of the universal. The worldview ensures the process of humanizing a person, transforming him into a self-worth and original world. The absence of a worldview as a holistic view of the world indicates the dehumanization of man, his degradation to a sub-human (animal) level of existence, distancing from his own essence. The anti-humanist essence of ideology is revealed as a closed inflexible system of dogmatic provisions, which creates a distorted quasi-religious picture of reality and considers a person exclusively as a means, not a goal. The key features of ideology in comparison with worldview are selectivity and fragmentation, intolerant attitude towards any "otherness". The other in the ideological picture of the world is an object of fear, hatred. The example of consumerism shows how ideology takes over worldview functions. A person, ideologically processed, mistakenly perceives an ideological system as a full-fledged authentic worldview, as a true picture of the world, and a system of values imposed by propaganda or manipulation as his own choice. It is shown that consumerism as a simplified and vulgarized ersatz form of liberalism as an existential dominant takes not simple consumption as a natural need, but an internal attitude to assert oneself through a demonstrative pathological desire to possess surplus. In the ideology of consumerism, a specific consumer mindset is formed, aimed at achieving social advantage through consumption; human happiness depends on the level of consumption, and consumerism itself becomes the goal and meaning of life. However, the given statistics of the international index of happiness show that there is no direct relationship between the level of consumption and an increase in the level of freedom, inner satisfaction, and meaningfulness.